2015
DOI: 10.1038/jp.2015.24
|View full text |Cite
|
Sign up to set email alerts
|

Lost in translation? English- and Spanish-speaking women’s perceptions of gestational weight gain safety, health risks and counseling

Abstract: Significant differences exist between Spanish- and English-speaking women's perception of GWG counseling, which may be due to language or cultural barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…Similar to our previous research with immigrant women of reproductive age, women in the current study felt that not being unable to communicate directly with healthcare professionals was frustrating and that this contributed to reduced communication and interactions [ 23 ]. Our findings concur with previous research showing that although the use of a professional interpreter for encounters with patients with limited English skills improves clinical care, patients’ satisfaction and outcomes with care received are diminished [ 36 , 37 , 38 ]. Study findings suggest that additional attention by healthcare providers should be given to minority women with limited language proficiency whom are at increased risk of excessive GWG such as Spanish- and Portuguese speaking pregnant women participating in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our previous research with immigrant women of reproductive age, women in the current study felt that not being unable to communicate directly with healthcare professionals was frustrating and that this contributed to reduced communication and interactions [ 23 ]. Our findings concur with previous research showing that although the use of a professional interpreter for encounters with patients with limited English skills improves clinical care, patients’ satisfaction and outcomes with care received are diminished [ 36 , 37 , 38 ]. Study findings suggest that additional attention by healthcare providers should be given to minority women with limited language proficiency whom are at increased risk of excessive GWG such as Spanish- and Portuguese speaking pregnant women participating in our study.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, our participants reported a high degree of trust in their medical providers, which is consistent with other reports in the literature (Ferrari et al, 2013). Furthermore, many participants commented that their doctor told them how much weight they should gain but could not remember specific numerical goals, which aligns with the literature that shows a low knowledge of gestational weight gain guidelines across cultural contexts (McPhie, Skouteris, Hill, & Hayden, 2015; Olagbuji, Olofinbiyi, Akintayo, Aduloju, & Ade-Ojo, 2015), particularly for Spanish-speaking women (Smid, Dorman, & Boggess, 2015). Importantly, participants reported that their providers’ focus on the numerical guidelines for gestational weight gain was not as effective in changing behaviors like diet as was specific dietary instructions from their providers.…”
Section: Discussionsupporting
confidence: 64%
“…gain guidelines across cultural contexts (Mcphie, Skouteris, Hill, & Hayden, 2015;Olagbuji, Olofinbiyi, Akintayo, Aduloju, & Ade-Ojo, 2015), particularly for Spanish-speaking women (Smid, Dorman, & Boggess, 2015). It is important to note that participants reported that their providers' focus on the numerical guidelines for gestational weight gain was not as effective in changing behaviors such as diet as was specific dietary instructions from their providers.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that language may have been a barrier to effectively conveying this information. 23 There are many known biases in the way that humans conceptualize and interpret numbers and risk. Employing strategies to mitigate these cognitive biases will help to optimize consideration of treatment options.…”
Section: Initial Preferencesmentioning
confidence: 99%